Baggage Cart with Weighing Mechanism for Hotels and Airlines - Vishal Verma; Kuldeep Kumar; Rashmi Aggarwal; Tanvi Verma (Journal of Engineering Research and Sciences, 2024)
In this article, it has been proposed a functional design of Baggage Cart with Weighing Mechanism for Hospitality Industry based on empirical observations. This design is expected to promote and become one of the high demand products which can later be used especially by hotels and respective airlines. It has been often observed that travelers are always concerned about the maximum weight of their baggage allowed in order to board a flight. Because as per norms of airlines one needs to carry a specific amount of baggage in the flight, in case of extra weighed baggage carried by a guest, he/she is charged extra amount as per KG by the respective airline. Keeping this point in mind, travelers are always conscious about the weight of their baggage before boarding a flight to avoid the last-minute hassle of paying huge extra money, and sometimes they need to drop the necessary items out from the baggage to adjust the weight of the baggage. In hotels, a guest request to weigh his/ her luggage is dealt with in the following ways: The front office associate/porter first needs to fetch the baggage from the guest room and bring it up to the bell desk or need to drag it up till time office / receiving area where it is weighed on a heavy-duty weighing scale. It is the traditional way of measuring baggage. The traditional way is time-consuming, uncomfortable, and less suitable to support the need of the traveler. Hence, to minimize the time and efforts, we wanted to invent a mechanism that will help and reduce the burden of managing the separate weighing machine, and therefore we came up with a baggage cart with a weighing mechanism in it.
Keywords: Baggage Cart; Weighing Mechanism; Customer Satisfaction; Service Quality